Phosphoinositide 3‐kinases as accelerators and brakes of autophagy. (5th September 2013) - O′Farrell, Fergal; Rusten, Tor E.; Stenmark, Harald
<x xml:space="preserve">Abstract</x> Degradation of cytoplasmic material by autophagy plays a key role in protein homeostasis and metabolic control, as well as in the removal of intracellular protein aggregates, pathogens and damaged organelles. The concept of up‐ or down‐regulating this pathway pharmacologically in neurodegenerative diseases, infections, inflammation and cancer is therefore attractive. Among the key pharmacological targets in regulation of autophagy are the phosphoinositide 3‐kinases (PI3Ks), which mediate the phosphorylation of phosphatidylinositol (PtdIns) or PtdIns 4, 5‐bisphosphate in the 3‐position of the (phospho)inositol headgroup. The catalytic products, PtdIns 3‐phosphate (PtdIns3P) and PtdIns 3, 4, 5‐trisphosphate [PtdIns(3, 4, 5)P3], respectively, have opposing roles in autophagy. PtdIns3P, the product of class II and III PI3Ks, mediates the recruitment of specific autophagic effectors to the sites of origin of autophagic membranes and thereby plays an essential role in canonical autophagy. By contrast, PtdIns(3, 4, 5)P3, the product of class I PI3Ks, triggers the target of rapamycin signalling pathway, which inhibits autophagy. In this review, we discuss the functions of class I, II and III PI3Ks in autophagy and describe the protein effectors of PtdIns3P and PtdIns(3, 4, 5)P3 that promote or inhibit autophagy, respectively. We also provide examples of how PI3K‐mediated control of autophagy is relevant to an understanding of tumour suppression and progression.